Penambahan Berat Badan Ibu Selama Hamil Dengan Berat Badan Lahir Bayi Di UPT Puskesmas Dlanggu Kabupaten Mojokerto - Zulfa Rufaida; Sri Wardini Puji Lestari; Ika Yuni Susanti (Mulawarman University, 2020)
Women weight before pregnancy and weight gain during pregnancy are the main determinants of the baby's weight at the end. Women with low body weight (for example <55 kg) before pregnancy who achieved a slight increase in body weight (<4500 grams) during pregnancy had a higher incidence of giving birth to babies with low birth weight than mothers with greater weight who reached more a lot of weight gain during pregnancy (Benson, 2009: 135). The purpose of this study was to determine women weight gain during pregnancy with birth weight.This research design uses